Computer-aided method engineering designing CASE repositories for the 21st century - Dahanayake, Ajantha, 1954- (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2001)
Computer aided method engineering is about generation and use of information systems design techniques according to user needs. Some times such environments are called generic tools or MetaCASE. This book presents the methodology and architecture of a CASE repository.